PERANAN KEMASAN (PACKAGING) DALAM MENINGKATKAN PEMASARAN DIGITAL PRODUK USAHA MIKRO KECIL MENENGAH (UMKM) DI DESA FIRDAUS - Santi M Hasibuan; Fitri A Lestari; Junita Putri Rajana (Bajang Institute, 2022)
Community Service Partners in this activity are Micro, Small and Medium Enterprises (MSMEs) which are engaged in the business of producing and buying and selling snacks in Firdaus Village. This study aims to find out how the strategy for improving MSMEs is THE ROLE OF PACKAGING IN IMPROVING DIGITAL MARKETING OF MICRO SMALL MEDIUM ENTERPRISES (MSMEs) IN FIRDAUS VILLAGE. MSMEs in Firdaus Village have very minimal and conventional marketing and packaging that is unattractive. For this reason, MSMEs need to be given training on the importance of using digital marketing and attractive packaging so that their marketing system can be better so that they can expand the scope of their business targets and can support better sales activities. In addition, MSMEs are also given assistance in creating business accounts on digital media, namely digital media such as creating Facebook accounts, Shoppe and others, along with how to optimally manage these digital media. The outputs produced from this service are Social Media and Instagram accounts, scientific articles published in national journals, and activity reports. The method used is to provide training in the form of lectures and provide tutorials on creating an account on digital media and how to manage the digital media. From the results obtained in this activity, it is suggested that the use of this digital marketing strategy can be followed up with regular guidance so that it can be effective and optimal in supporting marketing activities and increasing MSMEs business sales.